2020
DOI: 10.2174/1875399x02013010042
|View full text |Cite
|
Sign up to set email alerts
|

Twelve Weeks of High-Intense Interval Training Enhance the Neuromuscular and Cardiorespiratory Performance of Elderly

Abstract: Background: Exercise is an effective non-pharmacological intervention for the enhancement of neuromuscular and cardiorespiratory health. In particular, High-Intense Intermittent Training (HIIT) has been implicated in health management; however, in specific populations such as the elderly, is needed more investigations. Objective: The aim is to determine the impact of HIIT in the neuromuscular and cardiorespiratory fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…For lower and upper body strength, the lowest effect sizes were observed for studies with limited study quality [16,19]. Outcome measures of upper body strength were heterogeneous: studies that applied push-ups or arm curls revealed extremely large effect sizes [14,37,38], whereas moderate effect sizes were found in studies measuring isometric grip strength [38,40] and isometric and [15]. Higher effects on upper body strength compared to lower body strength might be due to higher similarities of testing and training.…”
Section: Effects On Strengthmentioning
confidence: 97%
See 3 more Smart Citations
“…For lower and upper body strength, the lowest effect sizes were observed for studies with limited study quality [16,19]. Outcome measures of upper body strength were heterogeneous: studies that applied push-ups or arm curls revealed extremely large effect sizes [14,37,38], whereas moderate effect sizes were found in studies measuring isometric grip strength [38,40] and isometric and [15]. Higher effects on upper body strength compared to lower body strength might be due to higher similarities of testing and training.…”
Section: Effects On Strengthmentioning
confidence: 97%
“…Fifteen out of 20 studies used a two-armed [14,16,17,19,31,[34][35][36][37][38][39][40][42][43][44], three studies a three-armed [18,29,40,41] and two studies a four-armed study design [13,15]. As it was part of the inclusion criteria, all studies applied standard randomization procedures for group assignment.…”
Section: Study Population and Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that regular physical activity can reduce neurological risk factors such as dementia [49], Parkinson's disease [50], frailty [51], and AD [52], which improve the quality of life [53]. Increased expression, secretion and downstream signalling of neurotrophic factors (BDNF, VEGF, IGF-1), reduced inflammation [54], and cardiovascular improvement, such as reduced arterial stiffness and lowered blood pressure [55][56][57][58], and cardiovascular improvement, such as reduced arterial stiffness and lowered blood pressure [57,59] are some of the mechanisms that could explain exercise-induced neuroplasticity. Taken together, all of these effects can contribute to the development of positive brain health, as shown in numerous studies [60][61][62].…”
Section: Discussionmentioning
confidence: 99%